Low Fructose and Low Salt Diets Increase Mitochondrial DNA in White Blood Cells of Overweight Subjects - Hernández-Ríos, R.; Hernández-Estrada, S.; Cruz-Robles, D.; Hernández-Lobato, S.; Villalobos-Martín, M.; Johnson, R. J.; Rodríguez-Castellanos, F.; Salazar, J.; García-Arroyo, F.; Sánchez-Lozada, L. G.; Madero, M. (Experimental and Clinical Endocrinology & Diabetes, 2013)
To evaluate the effect of sodium and fructose restriction on mitochondrial DNA (mtDNA) content and systemic oxidative stress in a sample of overweight and pre hypertensive subjects.Data and blood samples were collected from 36 overweight and pre hypertensive patients randomly assigned to either an isocaloric (with respect to baseline) low sodium-fructose diet or an isocaloric low sodium diet. Patients were followed for 8 weeks. We measured mitochondrial DNA (mtDNA) content from peripheral blood white cells by Real-time PCR and plasma malondialdehyde (MDA) and 2,4-dinitrophenylhydrazine (DNPH) as markers of reactive oxigen species (ROS).Compared to baseline, at week 8 there was a continued and significant increase in mtDNA in both the low sodium diet group [2.4 vs. 13.1 (relative copy number), p<0.05] and the low sodium diet-fructose group (1.9 vs. 147.2, p<0.05). By week 8 there was a continued decrease in plasma DNPH levels in the low sodium diet group (4.6 vs. 2.6, p<0.05) and in the low sodium diet-fructose group (5.8 vs. 2.2, p<0.05). No significant differences were found with MDA.Our studies suggest that simple dietary measures such as reducing salt with or without restricting fructose can increase mtDNA and improve markers of oxidative stress.
Keywords: fructose; obesity; mitochondrial DNA (mtDNA); reactive oxidative stress (ROS)